SukhaRakshak AI - anticipatory drought intelligence for India - Amarnath, Giriraj; Kapoor, Sanya; Bhatpuria, Dhyey; Padhee, Suman Kumar; Rao, K. V.; Sudhishri, S.; Sikka, Alok (International Water Management Institute, 2025)
India’s agriculture is highly vulnerable to drought due to its heavy dependence on monsoon rainfall, with nearly 68% of cultivated land at risk and the livelihoods of over 100 million smallholder farmers exposed. Past droughts in 1987, 2002, and 2015–16 resulted in significant food grain losses and GDP contractions, revealing deep structural vulnerabilities. Despite strong national institutions such as IMD, NDMA, CWC, and the Ministry of Agriculture and Farmers Welfare, drought management remains largely reactive, focused on post-impact relief rather than anticipatory action. Fragmented data systems, slow coordination, and limited localization of advisories constrain effective preparedness. Climate change is further intensifying drought risks, with rising temperatures, erratic monsoons, and higher evapotranspiration increasing the frequency and severity of agricultural droughts, as highlighted by IPCC projections for South Asia. Building on the South Asia Drought Monitoring System developed by IWMI and ICAR, SukhaRakshak AI bridges the gap between early warning and field-level action. By integrating AI, satellite data, forecasts, and contingency plans, it delivers hyper-local, predictive advisories in 22 Indian languages, enabling a shift from drought relief to resilience-driven, proactive management.